Jujuboside A Regulates Calcium Homeostasis and Structural Plasticity to Alleviate Depression-Like Behavior via Shh Signaling in Immature Neurons - Zhong Z; Liu J; Luo Y; Wu M; Qiu F; Zhao H; Liu Y; Wang Y; Long H; Zhao L; Wang Y; Han Y; et al. (Dove Medical Press, 2024)
Ziyan Zhong,1,* Jian Liu,2,* Yan Luo,1 Mei Wu,1 Feng Qiu,1 Hongqing Zhao,1 Yang Liu,1 Yajing Wang,3 Hongping Long,2 Lei Zhao,4 Yuhong Wang,1 Yuanshan Han,2 Pan Meng1 1Science & Technology Innovation Center, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of China; 2The First Hospital, Hunan University of Chinese Medicine, Changsha, Hunan, 410007, People's Republic of China; 3Office of Science & Technology, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of China; 4School of Integrated Chinese and Western Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuanshan Han, The First Hospital, Hunan University of Chinese Medicine, Changsha, Hunan, 410007, People's Republic of China, Email 121983755@qq.com Pan Meng, Science & Technology Innovation Center, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of China, Email 004181@hnucm.edu.cnBackground: Depression, a leading cause of disability worldwide, is characterized by dysfunction of immature neurons, resulting in dysregulated calcium homeostasis and impaired structural plasticity. Jujuboside A (JuA), a biologically active compound derived from Semen Ziziphi Spinosae, has demonstrated anti-anxiety and anti-insomnia properties. Recent studies suggest that JuA may be a promising antidepressant, but its underlying mechanisms remain unclear.Methods: Sprague-Dawley rats were subjected to chronic unpredictable mild stress (CUMS) to induce a depression model. JuA (12.5 mg/kg, 25 mg/kg, 50 mg/kg) was administered orally for 4 weeks. Emotional and cognitive function were assessed. Monoamine neurotransmitter levels were measured using enzyme-linked immunosorbent assay (ELISA). The number of immature neurons and calcium homeostasis were evaluated by immunofluorescence. Western blotting and immunofluorescence were employed to detect the expression of Sonic hedgehog (Shh) signaling proteins. Additionally, lentiviral vector expressing Shh shRNA (LV-Shh-RNAi) were infused intracerebrally to investigate the role of Shh in JuA's antidepressant effects.Results: JuA significantly ameliorated depressive-like behavior and cognitive dysfunction in CUMS rats, increased monoamine neurotransmitter levels in serum and hippocampal tissue, reduced the number of BrdU/DCX (bromodeoxyuridine/doublecortin)-positive immature neurons, and attenuated calcium ion (Ca2+) concentration and Ca2+/calmodulin-dependent protein kinase II (CaMKII) levels in immature neurons. JuA also markedly elevated synaptic density and prominence complexity, upregulated Shh, Gli family zinc finger 1 and 2 (Gli1/2), synaptophysin (Syn) and postsynaptic density protein-95 (PSD-95) expression in the ventral dentate gyrus (vDG). However, knockdown of Shh in the vDG counteracted JuA's therapeutic effects.Conclusion: These findings collectively suggest that JuA improves depressive-like behavior in CUMS rats by modulating calcium homeostasis and synaptic structural plasticity in immature neurons through the Shh signaling pathway.Keywords: Jujuboside A, Sonic hedgehog, Immature neuron, Calcium homeostasis, Depression